Class and state in ancien régime France : the road to modernity? - Parker, David, 1941- (Routledge, 1996)
David Parker's challenging interpretation presents a broad, in-depth study of the economic, social, ideological and political foundations of French Absolutism. This stimulating reassessment runs contrary to much revisionist historiography.